To Study the Nutrient Status in Soil and Plant after the Harvesting of the Tuber Crops under Three-tier Agroforestry System - Solanki, Vishnu K. (International Journal of Bio-resource and Stress Management, 2017)
An experiment was carried out to find out the nutritional status in soil and plants of tuber crops under Sapota-Jatropha based three-tier agroforestry system at the Agronomy Farm (Block-E), ASPEE College of Horticulture and Forestry, Navsari Agricultural University, Navsari (Gujarat) during rainy season 2011 and 2012. Statistically, experiment was laid out in randomized block design with six treatments and four replications. The seven years old plantation of Sapota (Manilkara acharas (Mill.) Fosberg) planted at 10×10 m spacing, with five year old plantation of Jatropha (Jatropha curcas L.) which was planted at 2.5×2.5 m spacing used for intercropping study. Three tuber medicinal plants viz., Kalihari (Gloriosa superba L.), Kali musli (Curculigo orchioides Gaertn) and Safed musli (Chlorophytum borivilianum Ker.) were selected for the present study. The observations viz. organic carbon, N, P, K, Ca, Mg, Fe, Mn, Zn and Cu in soil were analyzed after harvesting. Intercropping of Kalihari, Kali musli and Safed musli recorded higher nutrients viz., organic carbon, N, P, K, Ca, Mg, Fe, Mn, Zn and Cu in soil as compared to sole crop. Similarly higher organic carbon, N, P, K, Ca, Mg, Fe, Mn, Zn and Cu in plant was recorded under Sapota-Jatropha as compared to sole crop of kalihari, kali musli and safed musli. The trend was same in both the years as well as in pooled.